Frequency of chest pain in primary care, diagnostic tests performed and final diagnoses. Issue 21 (20th June 2017) - Hoorweg, Beatrijs BN; Willemsen, Robert TA; Cleef, Lotte E; Boogaerts, Tom; Buntinx, Frank; Glatz, Jan FC; Dinant, Geert Jan
Abstract : Objective: Observational study of patients with chest pain in primary care: determination of incidence, referral rate, diagnostic tests and (agreement between) working and final diagnoses. Methods: 118 general practitioners (GPs) in the Netherlands and Belgium recorded all patient contacts during 2weeks. Furthermore, patients presenting with chest pain were registered extensively. A follow-up form was filled in after 30 days. Results: 22 294 patient contacts were registered. In 281 (1.26%), chest pain was a reason for consulting the GP (mean age for men 54.4/women 53 years). In this cohort of 281 patients, in 38.1% of patients, acute coronary syndrome (ACS) was suspected at least temporarily during consultation, 40.2% of patients were referred to secondary care and 512 diagnostic tests were performed by GPs and consulted specialists. Musculoskeletal pain was the most frequent working (26.1%) and final diagnoses (33.1%). Potentially life-threatening diseases as final diagnosis (such as myocardial infarction) accounted for 8.4% of all chest pain cases. In 23.1% of cases, a major difference between working and final diagnoses was found, in 0.7% a severe disease was initially missed by the GP. Conclusion: Chest pain was present in 281 patients (1.26% of all consultations). Final diagnoses were mostly non-life-threatening. Nevertheless, in 8.4% of patients with chest pain, life-threatening underlying causes were identified. This seems reflected in the magnitude and wide variety of diagnostic tests performed in these patients by GPs and specialists, in the (safe) overestimation of life-threatening diseases by GPs at initial assessment and in the high referral rate we found.